Statement on the Lancet Commission on Medicine, Nazism, and the Holocaust - Chelouche, Tessa; Czech, Herwig; Fox, Matthew A; Hildebrandt, Sabine; Lepicard, Etienne; Ley, Astrid; Offer, Miriam; Ohry, Avi; Reis, Shmuel P; Roelcke, Volker; Rotzoll, Maike; Sachse, Carola; et al. (The Lancet (British edition), 2023)
SH has received royalties from Berghahn Books for The Anatomy of Murder, honoraria from educational institutions for lectures about medicine and anatomy in Nazi Germany, and is an unpaid member of the Harvard Human Remains Research Review Committee and the American Association for Anatomy Task Force on Legacy Collections. AT has received royalties from Cambridge University Press for the book Social Mendelism: Genetics and the Politics of Race in Germany, 1900–1948, and an honorarium from the University of Leeds (Leeds, UK) for a lecture titled “Mendeling Jews: a history of racial genetics”. MKW has received a grant from the Macy Foundation for the implementation of this Lancet Commission's first teacher training fellowship; has received honoraria from educational institutions for lectures on medicine and the Holocaust, which he donates to his institution's fund to support programmes related to this history; serves as Co-Chair of the American Medical Association's Truth, Reconciliation, Health and Transformation Task Force (for which he receives an annual honorarium that he donates to his university); and is an unpaid member of the Fellows Council for the Hastings Center and the Advisory Council for Physicians for Human Rights.